Measuring the pollution terms of trade with technique effects - Jean-Marie Grether; Nicole A. Mathys (Fondation pour les études et recherches sur le développement international (FERDI), 2010)
The pollution terms of trade (PTT) index first introduced and estimated by Antweiler (1996) allows to identify if trade-embodied emissions are on average larger in exports than in imports. His empirical results were based on the tradecomposition (between-sector) part of the PTT and revealed rather paradoxically that exports of rich countries were on average dirtier than their imports. Using a new database on SO2 manufacturing emissions that includes variation of emission intensities across countries, sectors and over time, this paper extends the earlier work by identifying two additional effects: the between-country and the technique effect. As it turns out, these two effects run opposite to the between-sector effect, and more than compensate it. Hence, the overall pattern is that high income countries tend to have lower PTT indices, meaning that their exports are cleaner than their imports, while in low income countries the reverse is observed.
Keywords: F18; Q56; 330